Deletion of ErbB4 Disrupts Synaptic Transmission and Long-Term Potentiation of Thalamic Input to Amygdalar Medial Paracapsular Intercalated Cells - Asede, Douglas; Okoh, James; Ali, Sabah; Doddapaneni, Divyesh; Bolton, M. McLean (Frontiers in Synaptic Neuroscience, 2021)
Identification of candidate risk genes and alteration in the expression of proteins involved in regulating inhibitory neuron function in various psychiatric disorders, support the notion that GABAergic neuron dysfunction plays an important role in disease etiology. Genetic variations in neuregulin and its receptor kinase ErbB4, expressed exclusively by GABAergic neurons in the CNS, have been linked with schizophrenia. In the amygdala, ErbB4 is highly expressed in GABAergic intercalated cell clusters (ITCs), which play a critical role in amygdala-dependent behaviors. It is however unknown whether ErbB4 deletion from ITCs affects their synaptic properties and function in amygdala circuitry. Here, we examined the impact of ErbB4 deletion on inhibitory and excitatory circuits recruiting medial paracapsular ITCs (mpITCs) using electrophysiological techniques. Ablation of ErbB4 in mpITCs suppressed NMDA receptor-mediated synaptic transmission at thalamo-mpITC synapses and enhanced thalamic driven GABAergic transmission onto mpITCs. Furthermore, long-term potentiation (LTP) at thalamo-mpITC synapses was compromised in ErbB4 mutant mice, indicating that ErbB4 activity is critical for LTP at these synapses. Together, our findings suggest that ErbB4 deletion from mpITCs disrupts excitation-inhibition balance and learning mechanisms in amygdala circuits.